Identification of Landslide Precipitation Areas in Lagos Valley Using Analytical Hierarchy Model and Fuzzy Logic - Atrin Ebrahimi; Amir Ali Abbaszadeh; Fatemeh Noredin Mosa; Hamid Ganjaeian; Zahra Zangane Tabar (جغرافیا و پایداری محیط, 2013)
Landslides are considered as one of the domain processes that are the result of natural processes and human activities. These processes are among the most damaging natural hazards that have been accelerating as human manipulation of natural systems in recent decades. Considering that identification and segmentation of susceptible areas and risk zoning is an important step in assessing environmental hazards, this study evaluates the degradation status of the Lasm basin. In this research, the geomorphology, geology and human parameters of the basin have been evaluated first. Then, using the hierarchical analysis method (AHP) and the experts' opinion, the layers used are valued. After obtaining the weight of the layers by the AHP model, the weights obtained on the layers were applied and then the information layers were combined with the fuzzy logic model and a final map was obtained. The studied basin has been classified in 5 classes in terms of potential landslide in order to better distinguish and evaluate more easily. The results show that about 43% of the total area of the basin (about 129 km2) is located in the area with a high and very high potential for landslide, which is mainly located in the southern part of the basin (due to the availability of most conditions). Besides, the results showed potential occurrence of landslides in the studied basin is generally increased from north to south and from west to east.